Soil Erosion and Conservation in Parts of Bilaspur Dt., Madhya Pradesh - Rao, T.M (Journal of Soil and Water Conservation, 2022)
The soil which is derived by the weathering processes of the rocks is in turn eroded away by the same processes of denudation like heat and rain and wind etc.. It is something like robbing Paul and paying Peter. Sometimes rich fertile soils are eroded away leaving barren grounds unfit for any kind of cultivation, and thus the advance of such features goes unchecked as time passes. By this there will be reduction in cultivable lands which pose serious problems and threat to agriculture. In these days o: drought and reduction in good fertile cultivable soils, soil erosion is an unchecked enemy of a progressing Nation. Hence combating of soil erosion becomes necessarily a National cause. Good forests are also reduced due to this erosion.